Synthesis of Coconut Husk-derived Carbon-based Material for Methylene Blue Dye Removal - Darius Ching Lin, Kon (UNIMAS, 2025)
Industrial pollution continues to represent a significant environmental challenge, as the reckless discharge of pollutants into water bodies and the atmosphere poses substantial threats to ecological systems and human health. Among the various classes of waterborne contaminants, dyes represent a particularly persistent and hazardous pollutant. Despite the development of numerous wastewater treatment techniques aimed at mitigating dye pollution, many existing methods either generate secondary pollutants or require extended treatment durations, thereby limiting their efficiency and sustainability. In this study, a carbon-based adsorbent was successfully synthesized from coconut husk using a modified Hummer’s method for the effective removal of methylene blue dye from aqueous solutions. Scanning Electron Microscopy (SEM) analysis confirmed the porous nature of the synthesized material, while Energy-Dispersive X-ray Spectroscopy (EDX) characterization post-adsorption revealed a compositional shift to 62.51% of carbon, 3.04% of nitrogen, 30.15% of oxygen, 0.70% of sulfur, 0.82% of chlorine and 2.78% of iron. The adsorbent demonstrated a noteworthy methylene blue dye removal efficiency of 67.65% accompanied by an adsorption capacity of 10.15 mg/g and a final solution pH of 10. At an adsorbent dosage of 0.1 mg/L, the removal efficiency was recorded at 41.92%, thereby demonstrating the concentration-dependent nature of the adsorption process. Additionally, an increase in temperature was observed to enhance the adsorption rate, including the endothermic nature of the process. The adsorption kinetics exhibited a gradual increase in dye removal over time, ultimately achieving equilibrium within 24 hours. Isotherm modelling and kinetic studies demonstrated that the adsorption mechanism followed the Langmuir isotherm model, suggesting monolayer adsorption on a homogeneously distributed active surface. The pseudo-second-order kinetic model exhibited the strongest correlation with experimental iv data, thereby substantiating that the adsorption process is predominantly governed by chemisorption. These findings underscore the potential of coconut husk-derived carbon-based material as an effective, cost-effective, and sustainable alternative for the treatment of dye contaminated wastewater.